AN OPEN RANDOMIZED STUDY OF PATOLA KATUROHINYADI KASHAYAM IN ALCOHOLIC LIVER DISEASE - Pawar, Suryajeet; Kadam, Ruta; Jawale, Sharvari (International Journal of Ayurveda and Pharma Research, 2015)
Alcoholic liver disease (ALD) is a leading cause of morbidity and mortality in India. Chronic consumption of alcohol results in variations in alcohol metabolism, oxidative stress, antigenic adducts formation and acetaldehyde toxicity. These factors cause inflammation, fatty changes, fibrosis of liver cells and raising the transaminases in the blood. There is no specific treatment for ALD. Patola Katurohinyadi Kashayam, a classical Ayurvedic formulation has been reported by many practitioners to be effective in treatment of liver disorders. This study focuses on the effect of the Patola Katurohinyadi Kashayam in ALD for restoration of normal liver function by investigating 10 subjective and 5 objective parameters. As Patola Katurohinyadi Kashayam is Raktaprasadak, Yakritgami, Deepan, Jwaraghna, Kamalanashak and Pandunashak it was used as Trial Drug. Clinical Trials were conducted at Anandvan De-Addiction Centre, Pune. By random allotment method 20 well-diagnosed patients of ALD were included in both Control and Trial group each. The diagnosis of ALD was made by documentation of alcohol excess and evidence of liver disease. Trial group was administered the Trial drug in a dose of 15ml with luke warm water after meal for the duration of 28 days. Control group was not given any drugs but observed for 28 days for all parameters. The statistical analysis revealed that Trial drug is effective in ALD and significantly reduces Panduta, Agnimandya, Hrullas, Daha and Daurbalya. Besides it significantly lowers the SGOT and SGPT levels too.